2023
DOI: 10.1111/ssqu.13261
|View full text |Cite
|
Sign up to set email alerts
|

The causal nexus between innovation and economic growth: An OECD study

Abstract: Innovation contributes to economic growth by generating new ideas and improving production processes. At the same time, countries with high economic growth have the freedom to promote innovation. This article aims to examine the causal relationship between innovation and economic growth. Method: An innovation index was constructed using factors of innovation, utilizing principal component analysis. The study used Granger causality to investigate the causal relationship between innovation and economic growth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In this process, employees expand their cognitive and perceptual scope by revisiting their existing knowledge structures and may experiment with nontraditional adaptations and combinations of ideas to mobilize innovative behaviors (Fredrickson, Mancuso, Branigan, and Tugade, 2000). Knowledge dissemination is a vital factor in economic development (Dhar et al, 2023). Research showed that according to the cognitive-emotional personality system theory, employees are able to complete their work with a sense of responsibility and pride when they are highly engaged in their work, are courageous and persistent and this state of high cognitive activity and arousal can promote their innovative behavior (Banks, Woznyj, and Mansfield, 2021).…”
Section: Work Engagement and Employee Innovation Performancementioning
confidence: 99%
“…In this process, employees expand their cognitive and perceptual scope by revisiting their existing knowledge structures and may experiment with nontraditional adaptations and combinations of ideas to mobilize innovative behaviors (Fredrickson, Mancuso, Branigan, and Tugade, 2000). Knowledge dissemination is a vital factor in economic development (Dhar et al, 2023). Research showed that according to the cognitive-emotional personality system theory, employees are able to complete their work with a sense of responsibility and pride when they are highly engaged in their work, are courageous and persistent and this state of high cognitive activity and arousal can promote their innovative behavior (Banks, Woznyj, and Mansfield, 2021).…”
Section: Work Engagement and Employee Innovation Performancementioning
confidence: 99%
“…Understanding the importance of the designated role of SD in the composition of the joint venture, research is relevant in the field of finding methods for diagnosing these elements, as well as developing measures to extend their service life, however, new technology is directly tied to innovation, and new technology encourages more invention (Dhar et al, 2023). This topic is especially relevant because the world, more and more small and large solar power plants have recently appeared, where this problem can manifest itself.…”
Section: Introductionmentioning
confidence: 99%